Are characteristics of sharia supervisory boards able to improve the performance of islamic banking? - Fitriana, Ratna; Yulianto, Agung; Solikhah, Badingatus (Journal of Islamic Accounting and Finance Research, 2019)
Purpose - The purpose of this study was to examine the effect of characteristics of Sharia Supervisory Board (DPS) such as DPS scientific background, dual positions of DPS, and the number of supervision days on the performance of Islamic banking. This paper also analyze profit sharing financing as an intervening variablMethod - The population of this study is Islamic Banks in Indonesia in 2012-2017 are 13 sharia bank. The selection of samples in this study using purposive sampling method and selected 8 banks. The data was analyzed using multiple linear regression analysis, path analysis, and sobel test.Result - The results showed that the number of DPS supervision days has a positive effect on the Sharia financial performance, multiple positions of DPS have a positive effect on profit sharing financing. The profit sharing financing is not able to mediate the relationship of the characteristics of the Sharia Supervisory Board to the Sharia financial performance.Implication - Islamic Commercial Banks in Indonesia suggest to improve the financial performance in accordance with sharia principles.Originality - This research is the first study that used intervening variable profit sharing financing.